2010
DOI: 10.1667/rr2030.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Mitigation of Acute Death of Mice after Abdominal Irradiation by the Antioxidant N-Acetyl-cysteine (NAC)

Abstract: Gastrointestinal (GI) injury is a major cause of acute death after total-body exposure to large doses of ionizing radiation, but the cellular and molecular explanations for GI death remain dubious. To address this issue, we developed a murine abdominal irradiation model. Mice were irradiated with a single dose of X rays to the abdomen, treated with daily s.c. injection of N-acetyl-l-cysteine (NAC) or vehicle for 7 days starting either 4 h before or 2 h after irradiation, and monitored for up to 30 days. Separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
5
35
0
1
Order By: Relevance
“…Non-abdomen body parts including the skeleton were shielded with a custom-made cerrobend block. We have reported that the shielding efficacy is >97.5% at a targeted single dose of 20 Gy, and the backscattered radiation (approximately 50 cGy) under this shielding plan does not induce detectable changes in bone marrow cell viability and activity ( 25 ).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Non-abdomen body parts including the skeleton were shielded with a custom-made cerrobend block. We have reported that the shielding efficacy is >97.5% at a targeted single dose of 20 Gy, and the backscattered radiation (approximately 50 cGy) under this shielding plan does not induce detectable changes in bone marrow cell viability and activity ( 25 ).…”
Section: Methodsmentioning
confidence: 95%
“…The mice were inspected twice a day and body weight was recorded daily for up to 14 days after the completion of irradiation. Radiation was delivered to the abdomen at a dose rate of 1.079 Gy/min (150 kVp and 6.6 mA) using a Faxitron X-ray Generating System (CP-160, Faxitron X-Ray Corp., Wheeling, IL) as described previously ( 25 ). Non-abdomen body parts including the skeleton were shielded with a custom-made cerrobend block.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation exposure is known to generate oxidative stress, and treatment with antioxidants can prevent radiation-induced injury. 35 Four months after irradiation, the percentage of CD45.2 peripheral blood cells was significantly decreased in mice transplanted with Nrf2 Ϫ/Ϫ BM compared with Nrf2 ϩ/ϩ BM ( Figure 2E). Therefore, the survival of Nrf2 Ϫ/Ϫ HSPCs is reduced after the induction of oxidative stress both in vitro and in vivo.…”
Section: Nrf2 ؊/؊ Bm Has Normal Basal Levels Of Ros But Increased Susmentioning
confidence: 94%
“…Metabolic function of vital organs, as determined by PET scan, may be preserved in TMI mice and could potentially be used as a non-invasive marker, similar to previously reported initiatives to assess organ toxicity by an FDG PET scan [2730]. Increased recovery of metabolic function after TMI may be a result of the gastrointestinal-protective effect of TMI [31]. These findings indicate significantly less intestinal damage in the TMI mice as compared to the TBI mice.…”
Section: Discussionmentioning
confidence: 72%